GENDER MAINSTREAMING IN TO COMMUNITY BASED DISASTER RISK MANAGEMENT - Iqbal, Muhammad Jawed; Baig, Muhammad Naseem; Sadia, Haleema; Khurshed, Muhammad Bilal; Saleem, Sadaf (European Scientific Journal, ESJ, 2013)
Although women are considered as the most vulnerable group in the society; but very little attention has been made to take into consideration the issue of gender sensitivity during the phase of Community Based Disaster Risk Reduction as well as Management in both natural and manmade disaster. In Pakistan a very limited number of organization are working to address the issue of mainstreaming of women in pre and post disaster activities. The goal of this paper is to synthesize and review the issue of disaster and gender mainstreaming. This paper highlights the gaps in terms of disaster preparedness by adopting CBDRM; and also critically analyzes the importance of the mainstreaming the element of gender in the phase of Disaster Mainstreaming overall in general and specific in the context of Pakistan. Recommendations and suggestions of the paper can be used to design and implement comprehensive CBDRM Preparedness Plan by mainstreaming the element of Gender sensitivity.